Comparative Evaluation of Two Audio-analgesic Tracks on Reduction of Anxiety Level in Patients Undergoing Root Canal Treatment: A Randomised Clinical Study - Ajay Singh Rao; Namrata Bajpai; Nimisha Chinmay Shah; Deebah Choudhary; Meetu Mathur; Vishnu Pratap Singh Rathore; Ridhhi Vasa (Journal of Clinical and Diagnostic Research)
Introduction: Patients often experience dental anxiety, which can range from mild apprehension to severe phobia. In addition to pharmacological treatments, methods like sedation, aromatherapy, behavioural techniques, and music therapy have proven effective in reducing anxiety. Music, in particular, has been well-studied in clinical settings. Aim: To compare the reduction in anxiety levels of patients undergoing endodontic therapy with two different audio-analgesic tracks. Materials and Methods: This randomised clinical study was carried out in the Department of Conservative Dentistry and Endodontics at KM Shah Dental College and Hospital, Vadodara, Gujarat, India, from May 2019 to November 2019. A total of 120 patients were enrolled in the study. Before initiating endodontic therapy, patients were assessed for baseline anxiety using the Visual Analogue Scale (VAS), along with measurements of Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), and Pulse Rate (PR). Participants were randomly divided into three groups: Group A: Om chanting music; Group B: weightless music; and Group C: control (no music). Vitals (SBP, DBP, PR) were recorded at three intervals: before treatment, at 30 minutes, and at one hour. The results were then statistically analysed using Statistical Packages of Social Sciences (SPSS) software version 22.0, employing the Analysis of Variance (ANOVA) test and Tukey’s Post-hoc analysis. Results: Out of the 120 patients, 82 (68.33%) were male and 38 (31.66%) were female, with a mean age of 35 years. The results indicated that SBP was significant during (p=0.004) and after treatment (p=0.002). Additionally, DBP was significant after treatment (p=0.037). PR was highly significant before, during, and after treatment (p<0.001 for all). The differences in SBP between groups B and C during treatment (p=0.003), as well as between groups A and C (p=0.004) and groups B and C (p=0.008) after treatment, were statistically significant. Additionally, a significant difference in DBP was observed between groups A and C after treatment (p=0.043). However, no significant differences in Heart Rate (HR) were found before, during, or after treatment among the groups (p>0.05). Conclusion: In the present study, both music tracks demonstrated clinically and statistically acceptable performance compared to the control group, with the Om chanting track having a more substantial influence on anxiety levels, SBP, and DBP than the weightless track. Additionally, there was a significant difference in HR, indicating the efficiency of music in reducing anxiety during dental treatment.